2013
DOI: 10.1155/2013/561290
|View full text |Cite
|
Sign up to set email alerts
|

Detoxification Combining Fasting with Fluid Therapy for Refractory Cases of Severe Atopic Dermatitis

Abstract: To introduce and determine the clinical benefits of a detoxification program that combines fasting with fluid therapy for refractory cases of severe atopic dermatitis (AD), we performed a retrospective chart review of inpatients with AD from March 2010 to February 2012 at the Department of Ophthalmology, Otorhinolaryngology and Dermatology of Korean Medicine in the Kyung Hee Medical Center. Patients were treated with the detoxification program, which combined fasting with fluid therapy, and herbal medicine, he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…The synthesis rate of IL4 /IFNγ increased [22]. Kim et al reported 7 adult AD patients with refractory skin symptoms treated with detoxification combining fasting with fluid therapy [23]. The findings are thoughtprovoking, yet due to the low number of reported patients, a clear correlation between short or long-term fasting and an improvement of AD symptoms cannot be shown -further controlled investigations are necessary to confirm it.…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis rate of IL4 /IFNγ increased [22]. Kim et al reported 7 adult AD patients with refractory skin symptoms treated with detoxification combining fasting with fluid therapy [23]. The findings are thoughtprovoking, yet due to the low number of reported patients, a clear correlation between short or long-term fasting and an improvement of AD symptoms cannot be shown -further controlled investigations are necessary to confirm it.…”
Section: Discussionmentioning
confidence: 99%